Evidence from cauliflower mosaic virus virion DNA for additional discontinuities in the plus strand. - Maule, A J (1985)
Two-dimensional electrophoresis of cauliflower mosaic virus (CaMV) virion DNA and analysis of Southern blots using (+) strand-specific probes to the 5' termini of the beta (5.4 Kb) and alpha (2.6 Kb) strands, revealed the presence of molecules in addition to those predicted from the known structure of CaMV DNA. The presence of 8 Kb molecules of (+) sense after denaturation suggested that a small proportion of circular molecules have only a single discontinuity in the (+) strand. Other molecules, probably 5' coterminal with the beta strand but smaller than 5.4 Kb, indicated that a minority of the circular full length CaMV DNA contain additional gaps in the (+) strand. Consequently, molecules equivalent to the remainder of the beta strand could be identified using a single strand probe for a region towards the 3'-end of the beta strand. Computer analysis of the nucleotide sequence of CaMV DNA in the region of the proposed additional discontinuities revealed regions displaying some homology with the major (+) strand priming sites at the 5' ends of the beta and alpha strands. It is our contention that the additional (+) strand molecules of beta specificity are a consequence of minor (+) strand priming sites.